2020
DOI: 10.1097/gox.0000000000002893
|View full text |Cite
|
Sign up to set email alerts
|

Certification and Accreditation in Plastic Surgery Subspecialty Training

Abstract: Summary: There are multiple subspecialties that residents can pursue after core plastic surgery training, including 5 major fellowship categories: aesthetic, burn, craniofacial, hand, and microsurgery. Hand surgery remains the only plastic surgery subspecialty to date, with a formal accreditation process following fellowship. The purpose of this study was to review the literature regarding the accreditation and match process of plastic surgery fellowship programs, the process of hand surgery certif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…This wide breadth draws many aspiring surgeons to the specialty. Plastic surgery subspecialties for which fellowship training is offered include craniofacial, hand, esthetic, microsurgery, burn, and gender-affirmation 1. The Accreditation Council for Graduate Medical Education (ACGME) only offers accreditation for 2 plastic surgery subspecialties: craniofacial and hand surgery 2.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This wide breadth draws many aspiring surgeons to the specialty. Plastic surgery subspecialties for which fellowship training is offered include craniofacial, hand, esthetic, microsurgery, burn, and gender-affirmation 1. The Accreditation Council for Graduate Medical Education (ACGME) only offers accreditation for 2 plastic surgery subspecialties: craniofacial and hand surgery 2.…”
mentioning
confidence: 99%
“…Plastic surgery subspecialties for which fellowship training is offered include craniofacial, hand, esthetic, microsurgery, burn, and gender-affirmation. 1 The Accreditation Council for Graduate Medical Education (ACGME) only offers accreditation for 2 plastic surgery subspecialties: craniofacial and hand surgery. 2 While plastic surgeons may practice in a variety of settings, subspecialties that are most strongly associated with a career in academia are craniofacial surgery, microsurgery, and hand surgery.…”
mentioning
confidence: 99%
“…Location is an important factor for any first job, as it impacts family life, salary, future career prospects, and self-esteem 9 . Due to the uneven distribution of plastic surgery subspecialties in the United States, the location of the first job plays a crucial factor as trainees decide on applying to plastic surgery residency or fellowship programs 3 . The location of a residency training program may also contribute to the subspecialty exposure in residency training—for example, some programs have greater exposure to cosmetic or transgender surgeries due to the patient population or state guidelines in a certain city.…”
mentioning
confidence: 99%
“…2 Some fellowship specialties, such as aesthetic plastic surgery or microsurgery, may have limited Accreditation Council for Graduate Medical Education accredited training programs in the United States and thus limit the locations that a graduate can train. 3,4 Prior studies have shown that a medical applicant's most critical factor for future training is geographic location. 5,6 Specifically, they prefer to train in an area that is geographically similar to where they previously trained.…”
mentioning
confidence: 99%
See 1 more Smart Citation